Severe thrombocytopaenia secondary to COVID-19. Issue 9 (15th September 2020) - Patel, Trupesh; Stanton, Noah; Gkikas, Ioannis; Triantafyllopoulou, Diana Ioanna Dionysia
Abstract : The SARS-CoV-2 infection has caused a pandemic with a case rate of over 290 000 lab-confirmed cases and over 40 000 deaths in the UK. There is little evidence to inform the optimal management of a patient presenting with new or relapsed acute idiopathic thrombocytopaenic purpura with concurrent SARS-CoV-2 infection. We present a case of severe thrombocytopaenia complicated by subdural haematoma and rectal bleed associated with COVID-19. A 67-year-old man, admitted with a non-productive cough and confusion, was found to be positive for COVID-19. Ten days after admission, his platelets decreased from 146×109/L to 2×109/L. His platelets did not increase despite receiving frequent platelet transfusions. He was non-responsive to corticosteroids and intravenous immunoglobulins. Romiplostim and eltrombopag were given and after 9 weeks of treatment, his platelet count normalised. He was deemed medically fit with outpatient follow-up in a haematology clinic.